Investigations on development of early distresses on bituminous pavement in India and remedies. Issue 2 (30th July 2021) - Sandra, Amarendra Kumar; Nallana, Nirmal Kumar
Abstract : In the present study, reasons for early distresses noticed on the bituminous pavement of a four-lane divided highway between the Pardi and Agrasen sections of National Highway 6 from km 498.000 to km 544.000, in India, were investigated. The total length of the road project is 46 km. A detailed pavement condition mapping was carried out, and various distresses were noticed on the surface. To assess the reasons for the distresses, combined cores of the bitumen surface course and the base course were taken from 57 locations, 29 on the left-hand side and 28 on the right-hand side of the carriageway, and mix properties were evaluated in the laboratory. The investigation on the mixes revealed that bituminous cores collected from both the surface course and binder course have no resemblance to the job mix formula. Non-homogeneity of layer thicknesses, variation in mix properties, variation in aggregate gradation and high filler–binder ratios were observed. Aside from the laboratory investigation, the physical condition of bitumen cores was studied and the conditions of the pavement layers were assessed based on the deflection basin parameters. This paper presents a systematic procedure adopted for identifying the causes of early distresses, and appropriate treatments are suggested for rectification.